Bacterial Associates of a Gregarious Riparian Beetle With Explosive Defensive Chemistry - McManus, Reilly; Ravenscraft, Alison; Moore, Wendy (Frontiers in Microbiology, 2018)
Bombardier beetles (Carabidae: Brachininae) are well known for their unique explosive defensive chemistry. These beetles are found in riparian corridors throughout the American Southwest, where they commonly form large diurnal multispecies aggregations in moist areas under rocks, in crevices, and in leaf litter. Using high throughput 16S amplicon sequencing, we provide the first microbiome survey of a bombardier beetle, Brachinus elongatulus, collected from two sites in Arizona. Two bacterial taxa were present in all individuals sampled: Enterococcus and Dysgonomonas. Enterococcus has been implicated in the production of fecal aggregation pheromone components, which have been shown to regulate aggregation in the German cockroach; it is possible that Enterococcus plays a similar role in Brachinus. Dysgonomonas was found in all the defensive cells and gut samples. Additional studies are needed to determine if these microbes play a role in these beetles’ unique chemical defense. Our results also show that the majority of B. elongatulus individuals collected from both sites were infected with Spiroplasma. Many Spiroplasma are intracellular, vertically transmitted insect symbionts that may manipulate host reproduction (e.g. cause male-killing) or provide resistance to nematodes or parasitoid wasps. Defensive protection could be especially beneficial to B. elongatulus, which are frequently parasitized by horsehair worms (Nematomorpha). Our findings suggest testable hypotheses on the role of these bacteria in bombardier beetle behavior and physiology.